Seamounts : (Blackwell Pub., 2007)
Seamounts originate from volcanic islands that have sunk beneath the surface of the sea, mainly as a result of erosion, or geological disturbance. The ecological and oceanographic importance of seamounts for the status of marine food webs and biodiversity has only recently been recognized, yet seamounts world-wide have been so intensively exploited by fisheries that many of their biotic components have suffered serious depletion. This important book brings together our current knowledge of seamounts, concentrating on the themes of recruitment and vulnerability of seamount organisms, impacts on seamount biodiversity, and the sustainability and economic basis of seamount fisheries. Chapters which are written by acknowledged experts in marine and fisheries ecology include coverage of the influences of ocean currents, complex food web structures, transient feeding by visitors to seamounts such as whales and tunas, and the integration of differing environmental compartments stratified by depth. The editors of this book have drawn together an extremely valuable reference and tool for all those involved in marine ecosystems, and fisheries conservation and management.